(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Three yearling intact males of Sudan desert sheep (Hamariecotype) ranging in weight between 26 and 30 kg were used in a 3x3 latinsquare design with the objective of studying the effect of feeding threecrude protein (CP) levels (14.5%, 16.7% and 18.7%) in complete iso-caloric molasses-based diets on nitrogen-balance, digestibility ofnutrients, rectal temperature and respiration rate. Nitrogen (N) level hadno significant effect on the digestibility coefficients of the differentnutrients, total digestible nutrients (TDN) and N-balance. Urine volume,rectal temperature and respiration rate were not affected by N level.